“Scrumbear” framework for solving traditional scrum model problems - Leanah Alsaber; Ebtesam Al Elsheikh; Sarah Aljumah; Nor Shahida Mohd Jamail (Bulletin of Electrical Engineering and Informatics, 2021)
Software engineering is a discipline that is little understood by people. It defines how software is developed and maintained to meet the clients’ requirements. Software engineers follow certain systems and standards in their work to meet the clients’ desires. It is on this background that engineers follow specific models in coming up with the final product. One of the models highly used is scrum, which is one of the agile methodologies. However, despite being highly used, it has inherent flaws that need to be corrected. Those flaws are product owner continues changing; do not accept changes in working scrum, sprint’s release time limitation, finally wasting team time within each sprint. This paper presents a new framework, which is an updated version of the current Scrum, to overcome the scum models mentioned issues. In this study, a new framework is presented in a way that is understandable and needed by software developer’s team upon the collected qualitative and quantitative data. The implementation was by making some changes to the current scrum model leading to the “Scrumbear”, certain flaws can be corrected. One of the presented changes involve adding the control master rule to ensure controlling the requirements changing.